Reservoir Sediment Inflow Prediction using Integrated Rainfall-Runoff and Discharge–Sediment model - Razad A.R, Abdul; L.M, Sidek; H, Basri; J.L, Alexander; K., Jung; S.K, Sinnakaudan (International Journal of Engineering and Technology, 2018)
Reservoir sedimentation adversely affects both operation and safety of dam. It is important for reservoir manager and operator to predict the incoming sediment inflow into a reservoir to develop sustainable sediment management plan. Continuous sediment monitoring is preferred to estimate total sediment load but it is labor intensive and costly. To cope with these limitations, total sediment inflow into a reservoir is predicted by coupling the runoff from hydrological model and sediment rating curves derived from field sampling dataset. In this research, MIKE NAM rainfall runoff model is used to simulate runoff in Cameron Highlandsâ€™ catchment, using hydrological data from 1999 to 2012. This model is calibrated and validated using the flow data of Sg Bertam. Field sampling is conducted to measure the Total Suspended Solids (TSS), Bed Load and grab samples at major rivers namely Sg Telom, Sg Habu, Sg Ringlet and Sg Bertam. Sediment rating curves using power function are used to describe the relationship between the total sediment load and discharge. Using this concept, annual total sediment inflow into Ringlet Reservoir from 1999 to 2012 is estimated in the range of 100,000 m3/year to 270,000 m3/year, agreeable to the survey records previously.Â Â